Integrating Circular Economy and Community-Based Governance for Sustainable Coastal Waste Management in Batam Coastal Community - Safitri, Dian Prima; Sholeh, Chaereyranba; Niko, Nikodemus; Setiawan, Ramadhani; Kurnianingsih, Fitri; Ramadhanti, Suci (Universitas Padjadjaran, 2026)
Coastal areas and small islands, such as the Riau Islands Province, face persistent challenges in waste management. Batam City experiences high household waste generation and severe plastic pollution, threatening local ecosystems and socio-economic resilience. Contributing factors include geographic isolation, limited infrastructure, and weak monitoring systems. This study uses an integrative framework that links circular economy principles with community-based governance in the context of coastal waste management in island regions. The novelty of this study is the development of an adaptive governance network model that integrates three dimensions of empowerment, namely psychological, organizational, and communal, with circular economy mechanisms to transform waste into economic assets. Using a qualitative case study through observation, interviews, and document analysis, findings reveal a fragmented, multi-actor landscape where corporate social responsibility programs, grassroots waste banks, government facilities, and interventions by non-governmental organizations operate independently with limited coordination. Despite existing capacities, the absence of inter-organizational collaboration has led to low waste sorting rates, reaching only 18%. The study proposes establishing an institutional platform for multi-stakeholder collaboration that integrates circular economy principles with community empowerment. Such a coordinated governance network can support sustainable coastal waste management and contribute to ecosystem restoration in Batam City.